THE LATE PLEISTOCENE APENNINE CHAMOIS FROM GROTTA MORA CAVORSO (SIMBRUINI MOUNTAINS, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
This paperdescribes a sub-entire, partially articulated skeleton of chamois found togetherwith other vertebrate remainsina silty lens withlimestone clastsbetween the 104 and 105 SSUU of Grotta Mora Cavorso(Latium, Italy). Thissilty lensis chronologically correlatable to a temperate oscillation of MIS 3.The skull and post-cranial remains from Grotta Mora Cavorso were compared with the fossil remains of chamois from numerous Late Pleistocene and older Holocene sites of Italy and of Pyrenees and Iberian Peninsula. Additional comparisons were made with large samples of extant chamois, Rupicapra pyrenaica ornata , R. pyrenaica pyrenaica and R. rupicapra rupicapra .Morphological and morphometric features of the skull and the horn-core, as well as other characters of the metacarpus suggest to refer the fossil remainsfrom Grotta Mora Cavorsoto Apennine chamois, R. pyrenaica ornata . This is the earliest ascertained recordin Central-Southern Italyofthe ornata -like chamois, a subspeciesso far knownwith certaintyonly in the Holocene, orpossibly in the Lateglacial.